Pengaruh Likuiditas, Profitabilitas dan Leverage Terhadap Nilai Perusahaan: Studi Pada Perusahaan Sektor Energi - Wiguna, I Putu Arta; Wijaya, Putu Yudy; Dewi, Ida Ayu Sasmita (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study examines the relationship between the value of energy sector companies listed on the Indonesian Stock Exchange from 2018 to 2022 and leverage, profitability, and liquidity. Purposive sampling was utilized in the Indonesia Stock Exchange (BEI) Energy Sector Companies study, which included 77 data samples. There is utilization of secondary data. The exam is structured like an assumption test. Multiple linear regression analysis is the method used. There were also runs of the F, t, and coefficient of determination tests.After examination, these results were reached: (1) Liquidity and company value do not correlate; (2) Profitability and company value exhibit a significant positive relationship; (3) Leverage and company value exhibit a positive and significant relationship; and (4) Leverage, profitability, and liquidity significantly influence company value. The researcher’s thesis is that since profitability and leverage have been shown to affect company value, investors and businesses should pay greater attention to boosting these factors.